Supersaturation-controlled morphology and phase evolution of NiCo LDH in controllable and continuous flow synthesis - Yan Hu (PLoS ONE, 2025)
This study demonstrates a controllable synthesis of NiCo layered double hydroxide (LDH) nanoplates via homogeneous coprecipitation in a continuous flow reactor (CFR). The CFR system enables precise control over LDH morphology and size by maintaining constant supersaturation under pseudo-steady-state conditions. We systematically investigated the relationships between supersaturation, nucleation processes, LDH growth, and morphological evolution, identifying distinct thresholds for homogeneous and heterogeneous nucleation. The competition between nucleation and crystal growth drives morphological transitions from isolated nanoplates to nanoflowers with increasing supersaturation. Furthermore, we characterized the phase transition mechanism between coexisting brucite-like and LDH phases. Four key factors governing the transformation of NiCo mixed hydroxides to NiCo LDH were identified: supersaturation level, metal/alkaline ratio, heterogeneous nucleation, and dissolved oxygen concentration. These findings provide fundamental insights into the controlled synthesis of LDH materials with tunable morphologies for potential applications in energy storage and catalysis.